Association Between Vascular Endothelial Growth Factor (VEGF) +936C/T Polymorphism (rs3025039) and Preeclampsia Among Myanmar Pregnant Women - Khin Ei Ei Saw; Thit Sar Aye Mg Thann (Journal of Pregnancy)
Conclusion: There was no significant association between VEGF +936C/T polymorphism (rs3025039) and preeclampsia among Myanmar pregnant women. However, the findings of this study highlighted that individuals carrying either the CT genotype or the T allele are at a heightened risk of developing preeclampsia. Furthermore, it suggests a potential impact of the gene on the occurrence of preeclampsia, yet the data lacks sufficient evidence to establish statistical significance.